FOSTERING RATIONAL USE AND PROTECTION OF AGRICULTURAL LAND BY UKRAINIAN AGRICULKTURAL HOLDINGS - Komarivska N. M. (Pressing Problems of Public Administration, 2017)
The issue of impractical agricultural land use carried out by agricultural holdings was explored. The analysis of the holding company’s land bank was carried out. The factors that may contribute to protection and rational land use for agricultural holdings were determined. The state regulatory policy affecting agricultural holdings’ acting in terms of rational use and protection of agricultural land was studied.